Going global or going nowhere? Chinese media in a time of flux - Keane, Michael (University of Queensland, School of English, Media Studies & Art History, 2016)
This article focuses on how Chinese media industries have sought to expand into new territories, identifying several mechanisms by which Chinese cultural and media products are traded and consumed: namely finished content, co-productions, formats and online platforms. The article also considers the value of overseas location shooting for domestic programmes and acquisition of international media assets. The key idea that is discussed in regards to China's outward-bound trade mission is know-how. In respect to media production, producers tend to opt for risk avoidance rather than creative exploration. Consequently, Chinese producers, investors and practitioners are deficient in knowledge of international markets and audience perceptions because the government has chosen to intervene, select and guide Chinese products. The article suggests this is gradually changing.